Fragmentasi dan Rekonstruksi Gagasan Islamisasi Ilmu di Kalangan Muslim Milenial Indonesia - Fresyam Antika Ajeng (PT. Panca Publishing Indonesia, 2026)
This study examines the fragmentation and reconstruction of the Islamization of knowledge discourse among Indonesian Muslim millennials through a Systematic Literature Review (SLR). The research is grounded in the epistemological shift from the early generation’s Islamization project toward the dynamics of knowledge production in the digital and global era. Data were collected from reputable academic publications issued between 2000 and 2025 and analyzed using thematic-narrative synthesis to identify generational response patterns. The findings reveal three major spectrums of response: affirmative-normative, integrative-pragmatic, and critical-reflective. Fragmentation appears at epistemological, methodological, and terminological levels, particularly concerning the relationship between revelation and reason and its implementation within higher education. Nevertheless, the study also identifies a substantive reconstruction process oriented toward integration-interconnection paradigms, ethical and maqashid-based frameworks, and transdisciplinary approaches adaptable to the digital ecosystem. Thus, the Islamization of knowledge among millennials does not signify total deconstruction but rather a conceptual transformation emphasizing contextual relevance and social benefit. This research contributes to Islamic epistemology discourse by incorporating a generational perspective in understanding the contemporary renewal of knowledge in Indonesia.